Pathways of educational co-production: The relationship between parental involvement and children’s school participation in India - Alinsunurin, Jason P. (Animo Repository, 2019)
Most of the education sectors around the developing world face many challenges, the consequences of which significantly matter to its long-term development outcomes. Schools and communities are not exempted from facing wicked problems which affect equity, efficiency, and quality of education. In this essay, we aim to study one of the most basic relational features of education governance in the case of a developing country. We believe that by unearthing such salient features of specific education governance systems, it will allow us to understand how education outcomes relate to the highly localized and contextualized parental involvement patterns.We do this specifically within the context of a fragmented and constrained service delivery system by situating our research project within the public education system of India. The country presently has the world’s largest education sector, counting more than 250 million students in the most recent academic year. We exploit and link two waves of the India Human Development Survey (2004/5 & 2011/12), a series of two linked waves of a nationally representative survey of communities and households.Our results show that parental involvement is temporally and positively related with the school retention. A child whose parent is PTA member is 1.5 to two times more likely to be in school than those children who are not. Moreover, PTA membership is also among the most important correlate of school retention, along with on a wide variety of indicators on caste, schooling, and sanitation practices. Our contribution resonates with education policies concerning parental engagement, while being mainly methodological and empirical. We innovate by utilizing large-scale multi-period household surveys which offer generalizability about parental involvement at the national level. Our choice of India as a context also resonates with the education policy in developing regions, as parental cooperation for a long time is understood inadequately in similar/related contexts.